Analisis Wacana Kritis pada Podcast “Putusan MK: Palu Hakim Patah Berkeping” (LITERATUS, 2023)
The existence Constitutional Court decision regarding the requirements for registering Candidates for President and Vice President Republic of Indonesia has caused a number of controversies in society today. An issue Gibran Rakabuming Raka, Mayor of Surakarta, will take part in the 2024 Presidential Election as Candidate Vice President. However, the age threshold criterian 40 years is an obstacle for the son of President Joko Widodo. So, this was done by suing the Constitutional Court to revise the criteria for presidential election participants, especially regarding minimum age. This raises big questions regarding President Jokowi's relationship with the political dynasty, which made the controversial phenomenon increasingly discussed by the media. For this reason, this research uses a qualitative descriptive research method using a critical discourse analysis approach modeled by Teun A.Van Dijk analyzing text in Najwa Shihab's podcast with the title "Putusan MK: Palu Hakim Patah Berkeping" with a duration of 27 minutes 36 seconds which was uploaded on October 18, 2023, on Najwa Shihab's Youtube channel. The podcast discussion criticized the judge's decision which was interfered with by political interests. The results of the research show that democratic order is now increasingly shifting to the power held by political elites who are in power so that power they have can change laws and slowly break the spirit of democracy in Indonesia